Analiza działania systemu monitoringu sieci kanalizacyjnej miasta Głogowa - wstępne wyniki = Analysis of monitoring system activity in sewerage network of city Głogów - preliminary results - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an analysis of measurement system activity located in combined sewerage system and attached catchments. The influence of measurement planning on the obtained results has been shown. Errors made during assembly and configuration of measurement equipment has been shown.
Keywords: kanalizacja ogólnospławna; monitoring strumieni ścieków; monitoring opadów; combined sewer systems; flowrate monitoring; rainfall monitoring